ROS2 for beginners. - Renard, Edouard (Manning Publications, 2022)
In this course, and in a few hours, I will take you step by step from a complete beginner to a ROS2 developer who writes scalable robotics applications. Are you learning ROS2 from scratch? You might be asking yourself, "Where do I start? How do I learn this material? What to do first?" When I first started using the Robot Operating System (ROS), it was hard for me to answer those questions. Thus, learning ROS/ROS2 was difficult. But it doesn't have to be that way if you learn with the right resources. Also, something I noticed is that when people teach ROS2, they often make comparisons with ROS1. What if you don't know ROS1? I created this course so that you can properly learn ROS2 from the beginning, with no prior knowledge of ROS and without having to waste weeks or even months trying to find out what to do. After completing this course, you can say goodbye to the big learning curve everyone faces when learning ROS2. The course is structured so that you can follow it one step at a time and get everything you need in the right order. At the end of the course, you'll be confident enough to start your own ROS2 application. You will have the opportunity to work on a complete project using the Turtlesim simulation. This will help you practice more on everything you'll learn in the course. That will be your first real project from A to Z. Along the way, you'll also learn how to use ROS2 tools to debug your application, to monitor what's going on, and to build your code. With everything you'll learn, along with the best practices I'll give you, you will be ready to start any ROS2 project with a good foundation.